The Discrimination of Taiwanese-American Portrayed in Interior Chinatown by Charles Yu - Nur, M. Masduqi Ashfiyan (English Literature Study Program, 2023)
This research investigated the sociology of literature, especially regarding Taiwanese American discrimination in the Interior Chinatown novel by Charles Yu. This study aimed to describe the forms of discrimination in thenovel Interior Chinatown and explore the causal factors of discrimination in the novel Interior Chinatown. The method in this research was literary criticism using a sociological approach with an analysis of discriminationbased on a perspective by Thomas F. Pettigrew. This research's data source was the novel Interior Chinatown, published in 2020 with 257 pages. This research employed the theory of discrimination by Thomas F.Pettigrew. The results of this study were; (1) the forms of discrimination against Taiwanese Americans in the novel Interior Chinatown consist of two types: direct and indirect. Direct discrimination consists of seven formsof discrimination, namely: citizenship status discrimination, racial discrimination, physical violence discrimination, colorism discrimination, regional discrimination, age discrimination, and gender discrimination.Indirect discrimination consisted of five forms of discrimination, namely: government regulations regarding the prohibition of owning property for Taiwanese immigrants in the United States, government regulations onrestrictions on property ownership in the United States, government regulations on restrictions on types of work and the environment, government regulations on legal restrictions for Taiwanese immigrants,and the government's strict regulations on marriage to immigrants; (2) the causes of Taiwanese American discrimination in the novel Interior Chinatown consisted of two factors; they were stereotypes and prejudice.